2020
DOI: 10.3390/rs12244043
|View full text |Cite
|
Sign up to set email alerts
|

Field-Scale Characterization of Spatio-Temporal Variability of Soil Salinity in Three Dimensions

Abstract: Information on spatial, temporal, and depth variability of soil salinity at field and landscape scales is important for a variety of agronomic and environment concerns including irrigation in arid and semi-arid areas. However, challenges remain in characterizing and monitoring soil secondary salinity as it can largely be impacted by managements including irrigation and mulching in addition to natural factors. The objective of this study is to evaluate apparent electrical conductivity (ECa)-directed soil sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Then, the CLQ at different scales was evaluated. The spatial scale transformation models obtained through model construction are shown as follows, and the determination coefficient (R 2 ) is used to measure the model accuracy [33]: (1) y = 0.722x + 0.262 (R 2 = 0.934) and y = 0.851x + 0.150 (R 2 = 0.843) are the transformation model from county-scale to city-scale and provincial-scale;…”
Section: Multi-scale Clq Evaluation Based On Gismentioning
confidence: 99%
“…Then, the CLQ at different scales was evaluated. The spatial scale transformation models obtained through model construction are shown as follows, and the determination coefficient (R 2 ) is used to measure the model accuracy [33]: (1) y = 0.722x + 0.262 (R 2 = 0.934) and y = 0.851x + 0.150 (R 2 = 0.843) are the transformation model from county-scale to city-scale and provincial-scale;…”
Section: Multi-scale Clq Evaluation Based On Gismentioning
confidence: 99%
“…Most parts of North India show tremendous variation in temperature in terms of maximum, minimum, mean, monthly and daily range of temperature (Jiang et al, 2021). The current statistical data shows increase in temperature and economic damages in past forty years (H. Li et al, 2020). According to published sources of government information on climate change phenomena were detected a 0.13°C per decade rising trend (X. .…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this climatic imbalance, few cold weather events have been recorded but most of the studies showed warming trend in global climate (Zhang et al, 2021). Due to anthropogenic activities the physical environment has been disturb and as a result both the northern and southern hemispheres are getting warm (R. Li et al, 2020). According to a research finding, increase in greenhouse gases and industrialization have increased the earth's surface temperature have raised up to 0.7°C in last fifty years, with the 1990s being the warmest decade (J. .…”
Section: Introductionmentioning
confidence: 99%
“…The absence of studies in the study area based on these conditions leads to the complexity, when it comes to mapping the distribution of irrigation soil salinity and assessment [Ivushkin et al, 2019;Gebremeskel et al, 2018]. Large scales mapping spatial, temporal, and depth variability of soil salinity is one of the fundamental steps in salinity management at irrigation in arid and semi-arid areas [Li et al, 2020]. Usually, soil salinity monitoring is often carried out with intensive sampling from observation points and an appropriate interpolation method to estimate salinity values for unsampled locations [Laiskhanov et al, 2021].…”
Section: Introductionmentioning
confidence: 99%